Etiology and Prognostic Criteria for Liver Failure in Southeast China: A Multicenter Retrospective Cohort Study Between 2018 and 2020 - Chunyan Lyu; Jun Han; Naling Kang; Dawu Zeng; Chantsalmaa Davgadorj; Lina Ge; Meifang Zhou; Richeng Mao; Yan Yan (Gastroenterology Research and Practice)
Conclusions: The incidence of HBV-LF is decreasing annually. AT III, as an independent prognostic criterion, has excellent discriminative ability for the outcomes of the HBV-ALF subclass.